THE INFLUENCE OF DIGITAL MARKETING AND GREEN PROMOTION ON THE DECISION TO PURCHASE TOYOTA RAIZE - Rauf, Abdul; Tovtora S, Feba Dinova Dex; Sopiyan, Aldi (Universitas Muhammadiyah Tangerang, 2024)
The lifestyle of today's modern society fulfills the needs and desires to shop more efficiently, practically and easily. Developing technology makes consumers use technology to meet their daily needs by using information facilities, one of which is the use of the internet. In determining the purchase decision, an important thing to consider is the quality of service. The company provides quality service aims to provide convenience for consumers. This study uses an associative method with a quantitative approach. Based on the multiple regression test, it shows that the higher the value of Digital Marketing (X1) and Green Promotion (X2) simultaneously at a certain value, then it will increase the value of Purchase Decision (Y) at a certain value as well. The simultaneous effect of Digital Marketing and Green Promotion on Purchase Decision of Toyota Raize at PT Astra Internasional is significant. Partially Digital Marketing has a positive and significant effect on Purchase Decision of Toyota Raize, and Green Promotion has a positive and significant effect on Purchase Decision of Toyota Raize at PT Astra Internasional.